2000
DOI: 10.1080/000164800750001026
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Alterations in the Vestibulocerebellar System in Alzheimer's Disease - A Golgi and Electron Microscope Study

Abstract: Alzheimer's disease is one of the main causes of cognitive impairment in the presenium and senium. Despite increased efforts in investigations of the aetiological background of the disease, most of the pathogenetic mechanisms remain unclear. From the morphological point of view, neurofibrillary degeneration and neuritic plaques, the main hallmarks of Alzheimer's disease, are mostly seen in the hippocampus and the cortex of the cerebral hemispheres. In contrast, the cerebellum and brain stem demonstrate minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Parts of the cerebellum regions of MCI patients underwent structural degenerative (Baloyannis et al, 2000; Fukutani et al, 1997; Li et al, 1994; Sjöbeck and Englund, 2001; Wang et al, 2002), including reduction of Purkinje cell density, atrophy of the molecular and granular cell layer, and concentration of amyloid plaques in the cerebellar cortex (Wegiel et al, 1999). In a study that manually partitioned human cerebellum into four substructures, i.e., anterior, superior posterior, inferior posterior lobes, and corpus medullare on each hemisphere, the posterior cerebellar lobe experience significant volume reduction in AD patients (Thomann et al, 2008), leading to poorer cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the cerebellum regions of MCI patients underwent structural degenerative (Baloyannis et al, 2000; Fukutani et al, 1997; Li et al, 1994; Sjöbeck and Englund, 2001; Wang et al, 2002), including reduction of Purkinje cell density, atrophy of the molecular and granular cell layer, and concentration of amyloid plaques in the cerebellar cortex (Wegiel et al, 1999). In a study that manually partitioned human cerebellum into four substructures, i.e., anterior, superior posterior, inferior posterior lobes, and corpus medullare on each hemisphere, the posterior cerebellar lobe experience significant volume reduction in AD patients (Thomann et al, 2008), leading to poorer cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our investigations on the cerebellum because the cerebellum can be adversely affected in AD, as well as other neurodegenerative diseases [47,50,53,56,59,60,65,68,69,71], and cerebellar degeneration causes cognitive impairment [49,57-59,62,63,66,67,72]. Previous studies demonstrated significant structural, functional, and metabolic abnormalities in AD cerebella [57-59,82], including insulin and IGF resistance [30], similar to the findings in more traditional targets of AD, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar degeneration in AD is manifested clinically by gait instability and increased falling [66], and structurally, by significant atrophy of the posterior cerebellar lobes, which correlates with cognitive impairment [67]. The major histopathological features of AD cerebellar atrophy include, reductions in Purkinje cell population, atrophy of the molecular and granule cell layers [68], increased amyloid deposition and gliosis in the cortex [69]; increased ubiquitin-immunoreactivity in senile plaques and degenerating neurites [70]; extensive abnormalities in dendritic spine density and synaptic structure in vestibulocerebellar, visual, and auditory pathways [71,72]; and degeneration of cerebellar white matter fibers with loss of climbing fibers and presynaptic varicosities [73]. In aggregate, synaptic pathology, rather than neurofibrillary tangles and plaques, represents the main correlate of cerebellar degeneration in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise, SV cycling includes the loading of neurotransmitters into SVs, the SV trafficking to and docking at the active zone of presynapses, the releasing of neurotransmitters, and at last the endocytosis and recycling of SVs [104]. In addition to synaptic loss, dramatically decreased expression levels of SV proteins and their coding mRNAs have been discerned in vast areas of postmortem AD brains including most part of the neocortex, limbic system, basal ganglia, and cerebellum; and the changes have a strong correlation to cognitive impairment [19, 105111]. It should be mentioned that the severity of these changes varies; and the relatively AD sensitive brain regions such as hippocampus, frontal, temporal, and parietal lobes, where there are more severe Aβ deposition, tau pathology, and mitochondrial damages, are early affected areas and demonstrate a greater loss of SV proteins and their coding mRNAs [108111].…”
Section: Synaptic Transmission Changes In Admentioning
confidence: 99%